WORKERS’ MENTAL WORKLOAD IN INDONESIAN SMALL FOOD-PRODUCING BUSINESS: PRELIMINARY FINDINGS AT A CORN CHIPS BUSINESS - Rizky Luthfian Ramadhan Silalahi; Anis Lilian Sari; Putri Intan Sriwahyuni; Dhita Morita Ikasari; Riska Septifani; Ardaneswari Dyah Pitaloka Citraresmi; Panji Deoranto (J@ti Undip: Jurnal Teknik Industri, 2022)
This research investigated conditions of mental workload among workers in Indonesian small foodproducing business, and how work and workers characteristics might influence the workers’ mental workload. A corn chips business located in an industrial central of corn chips in Malang municipality, Indonesia was the research object, in which its seven workers were involved as participants. NASA-TLX measurement involving six mental workload subscales was deployed to observe the current state of workers mental workload, along with determination of mean WWL value as representation of mental workload level. Measured NASA-TLX subscales varied among tasks and subscales, with indications of exposures of mental workload to the workers. This was indicated by high ratings of Mental Demand, Temporal Demand, Effort, and Frustration subscales which reached 70, 80, 90, and 70, respectively. Mean WWL values were in the range of 46.00 to 70.67, with the highest value observed was on Task 2 with 70.67 and Task 5 has the lowest value of 46.00. It is suggested that tasks and workers characteristics could have different influence on the observed mental workload subscales ratings and WWL. This research provides base of understanding and findings on states of workers’ mental workload in Indonesian small food-producing business.